New anticancer medicines approved by the EMA in 2025 - Bege, Miklós; Borbás, Anikó (De Remediis, 2026)
Despite the serious progress in the antitumor therapy, cancer did not cease to be one of the leading causes of death in the developed world. Hence still there is high interest for new anticancer agents. In 2025, the EMA approved 104 new medicines, 37 of them containing new active substances. 18 new anticancer medicines were approved (14 new active substances).  In this review, we aim to shortly summarize the mechanism of action and use of the new drugs approved by the EMA in the year 2025.